A semiflexible polymer chain under geometrical restrictions: Only bulk behaviour and no surface adsorption - Mishra, P.K. (Condensed Matter Physics, 2014)
We analyse the conformational behaviour of a linear semiflexible homo-polymer chain confined by two geometrical constraints under a good solvent condition in two dimensions. The constraints are stair shaped impenetrable surfaces. The impenetrable surfaces are lines in a two dimensional space. The infinitely long polymer chain is confined in between such two (A and B) surfaces. A lattice model of a fully directed self-avoiding walk is used to calculate the exact expression of the partition function, when the chain has attractive interaction with one or both the constraints. It has been found that under the proposed model, the chain shows only a bulk behaviour. In other words, there is no possibility of adsorption of the chain due to restrictions imposed on the walks of the chain. Ми аналiзуємо конформацiйну поведiнку лiнiйного напiвгнучкого гомополiмерного ланцюга пiд дiєю двох геометричних обмежень в умовах доброго розчинника у двовимiрному просторi. Обмеження представляють собою непроникнi поверхнi схiдчастої форми. Непроникнi поверхнi є лiнiями у двовимiрному просторi. Нескiнченно довгий полiмерний ланцюг є обмежений двома поверхнями (A and B). Для розрахунку точного виразу статистичної суми використовується ґраткова модель повнiстю напрямлених блукань без самоперетинiв, якщо ланцюг має притягальну взаємодiю з одною чи двома поверхнями. В рамках запропонованої моделi отримано лише об’ємну поведiнку ланцюга. Iншими словами, жодної можливостi для адсорбцiї ланцюга пiд дiєю обмежень на блукання, не спостерiгається.